Cinema Africa 2023 - A conversation with Gudrun Columbus Mwanyika (A Conversation with ..., 2023)
Duncan Tarrant interviews the leading actor Gudrun Columbus Mwanyika of the film "Tug of War" that was presented at the 2023 Cinema Africa film festival in Bayreuth. Apart from being an actor Gudrun Columbus Mwanyika from Tanzania is also a producer and filmmaker. During the film festival he represented the movie "Vuta N‘Kuvute" (Tug of War) - a feature-length fiction based on Adam Shafis award-winning Swahili novel. The story explores a forbidden romance between star-crossed lovers against the backdrop of 1950s colonial Zanzibar. Young Indian-Zanzibari Yasmin flees from her arranged marriage and meets Dengé, a young revolutionary. Cinema Africa 2023 in Bayreuth was organised by the Africa Multiple Cluster of Excellence at the University of Bayreuth and curated by Prof. Dr. Ute Fendler.